Kualitas Layanan Pendidikan (Studi Kasus di LKP Poklamator Padang) - Rahmadona, Sahrasofi; Wirdatul 'Aini, Wirdatul 'Aini (Jurnal Family Education, 2023)
This research is motivated by the uniqueness of LKP Proklamtor Padang in maintaining the quality of service in education as evidenced by the large number of students who go to Japan. . This study aims to describe the quality of education services at LKP Proklamator Padang from the dimensions of responsiveness, empathy, tangibles, and reliability. This research uses a qualitative approach with a case study type. Data sources are instructors, Japanese language training participants and management staff of LKP Proklamator Padang. With data collection techniques using observation techniques, interviews, and documentation. The results of the research illustrate that: (1) the quality of educational services is seen from the dimensions of responsiveness between students and instructors who are open to each other in learning; (2) the quality of education services is seen from the dimensions of empathy the instructor gives attention, motivation, and good relations with students; (3) the quality of education services seen from the dimensions of physical evidence of instructors and students implementing health protocols and maintaining cleanliness and adequate facilities in learning; (4) the quality of education services is seen from the dimensions of instructor and student demands to apply rules, and apply justice to all students and instructors are responsible for reports on student learning outcomes.